The Stigmatization of Drug Addiction in South-East Turkey the Case of Drug Abuse Prevention Programme for Youth Project in Turkey - Wanke, Michal; Macit, Ruken; Gülerce, Hakan (Addicta: The Turkish Journal on Addictions, 2022)
Cannabis use undergoes a dynamic redefinition under selected legal frameworks globally. Many prevention programs face a dilemma between delivering abstinence objectives and pursuing more nuanced, harm reductionist aims. However, drug use in South-East Turkey is strongly stigmatized and is absent from the official life of the community, so neither of these discussions takes place. The authors participated in the development of a Drug Abuse Prevention programme for Youth and this article is grounded in qualitative data from Turkey. A follow-up study was conducted among the youth participants of a pilot phase of the program (n=20), developed by an international group of professionals in the form of an online workshop and video campaign. The data were collected by conducting a semi-structured qualitative interview. The participants live amid the omnipresence of drugs and simultaneously very actively detach themselves from it. There is a powerful taboo and families attempt to conceal the cases of drug use among them. They also stigmatize the users in order to distinguish themselves from the substance. It is counterproductive to talk about drug use to audiences who actively deny its presence within the community. The interventions ought to account for stigmatization to ensure realistic delivery